Influence factors of the Enterprise's Social Responsibility Development: A case study of the hotel and tourism sector in San Carlos, Costa Rica - Martínez Villavicencio, José (2015)
In the last years, small, medium and big companies from Costa Rica have intensified their interest in Corporate Social Responsibility (CSR). Given the sustainability and survival growing urgency in modern society, commercial activity assumes responsible and integral actions on the country development. The aim of this article is to identify the driving factors of CSR, which are, specifically, consumers, suppliers, community, environment, competitiveness and financing, to formulate management models and measurement indicators that could be used to influence and ease the responsible task of a company. For this purpose, we perform a case study within 16 hotel enterprises in La Fortuna de San Carlos, applying a qualitative methodology by semi-structured interview means. Our results indicate that the main driving factor of CSR is the consumers; in second place, the environment, while we found that suppliers and community don’t have relevant effect as a driving factor of CSR. This information allows us to support the creation of social policies and sustainable regional tourism.